Going "Fourth" From Medical School: Fourth-Year Medical Students' Perspectives on the Fourth Year of Medical School. (October 2015) - Benson, Nicole M.; Stickle, Timothy R.; Raszka, William V.
Abstract : Purpose: To learn what graduating medical students considered the primary purposes of the fourth year of medical school, their approach to residency selection, and the challenges they faced in meeting their fourth-year goals. Method: A 52-question Web-based survey was administered to fourth-year students from 20 U.S. MD-granting medical schools in spring 2014. Quantitative data were analyzed with one-way analysis of variance, chi-square analysis, or paired t tests. Responses to an open-ended question were coded into themes and confirmed. Results: A total of 1, 367/2, 884 (47.4%) students responded. Students applied to a mean of 36.4 (SD = 22.6) residency programs and interviewed at a mean of 12.3 (SD = 5.6) programs. Surgery applicants applied to more programs (mean = 58.2, SD = 22.3; P < .001); radiology applicants interviewed at more programs (mean = 16.9, SD = 8.5; P < .001). Students took a mean of 1.8 (SD = 0.8) monthlong away electives in their career specialty of choice; surgery and emergency medicine applicants were more likely to complete away electives ( P < .001). Students agreed the fourth year has multiple valuable purposes, including maximizing the likelihood of matching into their residency of choice, gaining a broad educational experience, and preparing for residency. The main purpose varied by specialty, but overall students ranked preparing for residency highest. Completing away electives and interviewing were expensive; approximately 35% of students could not complete away electives because of financial constraints. Conclusions: Medical students view the fourth year as a time for residency selection and preparation. Abstract : Supplemental Digital Content is available in the text.